Cechy indywidualne języka w felietonach z cyklu „Z życia polskich sfer” Henryka Martenki („Angora” 2015) - Kudra, Barbara (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article presents the individual characteristics of the language (idiolect/idiostyle) of the columns written by Henryk Martenka from “Angora” in 2015. These are among others: humour, irony, colloquial, lexical innovation, original epithets, styling, quotes with argumentative function, rhetorical strategy questions, making understatements. They demonstrate the originality, conceptualization of subsistence of his author, his consciousness and metalinguistic reflection and bring the reader closer to world’s attitudes, opinions and values.